Impairment of Intestinal Barrier Function Induced by Early Weaning via Autophagy and Apoptosis Associated With Gut Microbiome and Metabolites - Tang, Wenjie; Liu, Jingliang; Ma, Yanfei; Wei, Yusen; Liu, Jianxin; Wang, Haifeng (Frontiers in Immunology, 2021)
Early weaning piglet is frequently accompanied by severe enteric inflammatory responses and microbiota dysbiosis. The links between the gut microbiome and the etiology of gut inflammation are not fully understood. The study is aimed to investigate the potential molecular mechanisms mediating inflammatory reactivity following early weaning, and to find whether these changes are correlated with gut microbiota and metabolite signatures by comparison between suckling piglets (SPs) and weaning piglets (WPs). Histopathology analysis showed a severe inflammatory response and the disruption of epithelial barrier function. Early weaning resulted in reduced autophagy indicated as the suppression of autophagic flux, whereas induced the TLR4/P38MAPK/IL-1β-mediated apoptotic pathway, as well as activation of the IL-1β precursor. The alpha-diversity and microbial composition were changed in WPs, such as the decreased abundances of Bifidobacterium, Bacteroides, Bacillus, Lactobacillus, and Ruminococcus. Microbial co-concurrence analysis revealed that early weaning significantly decreased network complexity, including network size, degree, average clustering coefficient and number of keystone species, as compared with the SP group. Differentially abundant metabolites were mainly associated with amino acid and purine metabolism. Strong correlations were detected between discrepant microbial taxa and multiple inflammatory parameters. In conclusion, we found that dysregulations of autophagy and apoptosis pathway were involved in colon inflammation during weaned period, which may result from gut microbiota dysbiosis. This study may provide possible intervention modalities for preventing or treating post-weaning infections through maintaining gut microbial ecosystem integrity.